PERFORMANCE MEASUREMENT USING AN INTEGRATED MODEL OF SUPER EFFICIENCY MODELS AND MANAGERS PREFERENCES; THE CASE OF MASKAN BANK - Abdolrasool Ghasemi (فصلنامه پژوهش‌های اقتصادی ایران, 2010)
DEA models that calculate the efficiency index with respect to inputs and outputs are commonly used in recent years. Although flexibility is one of the key characteristics of DEA models, specially where data is abundant, they overestimate the efficiency in small samples. Furthermore, they do not take into account managers' relative preferences about inputs or outputs. In this study, the managers' preferences are derived from a survey completed by bank experts. Then analytical Hierarchy process (AHP) is used to the weight the outputs and inconsistency of expert views. Finally, the expert matrix is derived from consistent expert views by the weighted geometrical average. Results show that 85 percent of branches have the efficiency lower than 50 percent with 41 percent of branches having the efficiency lower than 25 percent.